Influence of breed and age on goat leather quality - Jacinto, Manuel Antonio Chagas; Dos Santos, Heid Sueli Leme; Pucci, Milton Cerqueira [UNESP] (My University, 2015)
The objective of this study was to determine the influence of the Anglo-Nubian, Alpine, and Saanen goat breeds, by comparing them at the ages of three months and six months, on the physical-mechanical properties of leather subjected to quality control testing. Thirty animals - five 3-month-olds and five 6-month-olds of each breed-were used. Skins were chrome-Tanned and re-Tanned with acrylic syntan. Six test pieces were taken from the leather in the backbone and belly regions, three in parallel and three in perpendicular directions to the backbone, to measure tensile strength and tear load, and another six samples were used for the distension of the grain by the ball burst test (lastometer), besides determination of pH, chromium oxide, and solubles in dichloromethane. Means from physical-mechanical testing were compared by Tukey's test at the levels of 1 and 5% probability. The longitudinal direction had a positive effect (P<0.05) on the tensile values of leather from the three breeds, two ages, and two regions, exceeding the minimum of 20 N/mm2. The tear load of the leather of all analyzed animals was over 40 N/mm, with a positive effect (P<0.05) of the transverse direction. The resistance of the leather from all studied animals to the distension of the grain by the ball burst test was over 10 mm. The mean values of chemical tests were within the established limits for good-quality leather, except for pH (3.41 and 3.48).
Keywords: Age; Breed; Goat; Leather; Quality